Case report: Novel FHR2 variants in atypical Hemolytic Uremic Syndrome: A case study of a translational medicine approach in renal transplantation - Stea, Emma Diletta; Skerka, Christine; Accetturo, Matteo; Pesce, Francesco; Wiech, Thorsten; Hartman, Andrea; Pontrelli, Paola; Conserva, Francesca; Castellano, Giuseppe; Zipfel, Peter F.; Gesualdo, Loreto (Frontiers in Immunology, 2022)
Atypical Hemolytic Uremic Syndrome (aHUS) is a severe microangiopathy with prevalent kidney involvement due to genetic or acquired (autoantibodies) abnormalities most of them affecting the complement alternative pathway. The genetic factors/alterations influence the clinical presentation, therapeutic response, and recurrence, especially after kidney transplantation. A 22-year-old man developed a severe form of systemic aHUS. The kidney biopsy showed thrombotic microangiopathy and signs of chronic renal damage. Despite two Eculizumab infusion the patient remained dialysis-dependent, and ESKD was diagnosed. Two novel rare variants c.109G>A (p.E37K), and c.159 C>A (p.Y53*) were identified in the FHR2 gene, and Western blot analysis reveal severely reduced of the FHR2 protein in patient’s serum. Although FHR2 involvement in C3G has already been reported, its role as complement modulator is not yet been entirely clarified. In addition, there are not cases of aHUS patients with FHR2 variants reported. Considering the role of FHRs in complement and the prospective of a kidney transplant, we evaluated the relevance of the low FHR2 plasma levels and performed functional in vitro assays to clarify if the low FHR2 plasma levels influence complement control at endothelial surfaces and to define a rational for a therapeutic approach in this unique patient. We showed that patient serum with low FHR2 levels leads to complement activation and C5b-9 deposition on human endothelial cells and affect cell morphology. As C5b-9 deposition is a prerequisite for endothelial cell damage these results suggest that extreme low FHR2 plasma levels enhance the risk for aHUS pathology. Given the ability to reduce C5b-9 deposition, both recombinant FHR2 and Eculizumab were tested in vitro to block hemolysis and protected the endothelial cell surface. Both components showed comparable profiles. Based on these results, the patient was transplanted and Eculizumab was used in the induction and maintenance therapy. Today 5 years after the transplantation, the patient is in god conditions, graft function is stable. A follow-up shows no disease recurrence. This case study represents, to our knowledge, the first case of aHUS patients carry FHR2 mutations and shows an example of a translational therapeutic approach in kidney transplantation.